Long-Term Outcomes of an Urban Farming Internship Program. (September 2016) - Sonti, Nancy Falxa; Campbell, Lindsay K.; Johnson, Michelle L.; Daftary-Steel, Sarita
Long-term impacts of an urban farming youth internship were evaluated in Brooklyn, New York. Alumni surveyed 1 to 9 years after program completion were enrolled in college or graduate school at higher rates than their peers and reported connections to the environment and healthy eating. Participants reported learning job skills through the internship, including farming practices, time and money management, teamwork, and public speaking. In addition, participants reported an increased sense of responsibility, high levels of self-confidence, and strong connections with their community. The amount of time spent in the internship positively affected attitudes and behaviors regarding communication and decision-making.